Decolonizing Religious Authority: A Comparative Typology of Ba‘alawi Religious Authority in Pekalongan - Luthfi Maulana; Muhandis Azzuhri; Marwan Hayeemaming; Abdul Basit (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
Studies on religious authority within the Arab diaspora in Indonesia have primarily focused on genealogical legitimacy, charismatic leadership, or organizational influence, while paying limited attention to how competing forms of religious authority are reconstructed through decolonial processes and socio-religious power relations. Addressing this gap, this study examines how Ba‘alawi religious authority is decolonized and rearticulated in contemporary Indonesia through the perspectives of Habib Rizieq Shihab (Islamic Defenders Front), Habib Luthfi bin Yahya (Nahdlatul Ulama), and Habib Ahmad Baqbarah together with Habib Ahmad Ridho Assegaf (Shi’a). Employing a qualitative phenomenological approach, data were collected through observation, in-depth interviews, and document analysis, and analyzed using decolonial theory in dialogue with Michel Foucault’s concept of power/knowledge. The comparative analysis of empirical data identified three distinct typologies of religious authority. The first is an Islamist model, which reconstructs religious authority through an integrative-formalistic understanding of Islam and the state while simultaneously engaging substantivist interpretations of Islamic political order. The second is a Moderate model, which legitimizes religious authority through nationalist discourse, devotion to the Ahl al-Bayt, and mawlid traditions as mechanisms for cultivating social cohesion and religious legitimacy. The third is an Ukhuwah model, developed within the Shi’a Ba‘alawi network, which reconstructs authority through the ethical teachings of Sayyidina ‘Ali ibn Abi Talib and promotes humanitarian solidarity across religious and social boundaries. These three typologies emerged from a comparative analysis of the actors’ religious narratives, organizational practices, and strategies for negotiating authority within Indonesian Muslim society. The study contributes to the scholarship on decolonial studies by demonstrating that the decolonization of religious authority is not a singular process of resisting inherited colonial structures, but a plural and contested process that generates multiple configurations of religious legitimacy and socio-religious power. It further extends debates on religious authority by proposing a comparative typology of Ba‘alawi authority that explains how competing decolonial projects reshape Islamic authority in contemporary Indonesia.